The great economists : a history of economic thought - Marshall, Howard Drake (New York : Pitman Pub. Corp., 1967)
This is the author's conviction that the student can best learn about the masters by reading their original works. The book covers the following topics: Early Economic Thinkers; Adam Smith - Beginnings of Political Economy; Malthus - Pessimism Personified; Ricardo - The Pessimistic View Continued; Mill and the Close of the Classical System; Marx and the Socialist Critics; The German Historical School; The Concept of Marginal Utility; Alfred Marshall and the Neoclassical System; Three American Institutionalists; Monopolistic vs. Imperfect Competition; The Economics of Capitalism; and The Present Generation of Economists.
Includes index.
Includes bibliographical references: p. 377-383.
rpm 07/11/2017
Loans
Keywords: Economics